Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/01457632.2015.1042341
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction and Analysis of Surface Transfer Coefficients on Moist Object During Heat and Mass Transfer Application

Abstract: Convective surface transfer coefficients data for a moist object are not easily available from the literature and this coefficient is usually assumed to be constant in most studies. A three-dimensional (3D) numerical model is developed for prediction of heat and mass transfer coefficients on the surface of the rectangular moist object. A computational fluid dynamics tool is used for flow analysis at three different higher velocities. The spatial distribution of heat and mass transfer coefficients is estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Such a 1:1 ratio lies within the typical range of values evaluated in previous studies(Kumar et al, 2014). The drying conditions for the base case are typical for forced convective drying(Ateeque et al, 2014;Chandramohan, 2015)(CHTC = 100 W/m 2 K) at elevated temperatures (T ref,d = 40°C) with dry air (RH ref,d = 10%). The conditions during tempering (CHTC = 10 W/m 2 K, T ref,t = 20°C) are typical for an ambient environment outside the dryer.…”
supporting
confidence: 74%
“…Such a 1:1 ratio lies within the typical range of values evaluated in previous studies(Kumar et al, 2014). The drying conditions for the base case are typical for forced convective drying(Ateeque et al, 2014;Chandramohan, 2015)(CHTC = 100 W/m 2 K) at elevated temperatures (T ref,d = 40°C) with dry air (RH ref,d = 10%). The conditions during tempering (CHTC = 10 W/m 2 K, T ref,t = 20°C) are typical for an ambient environment outside the dryer.…”
supporting
confidence: 74%
“…(2)) which is not accounted for in the wet bulb temperature predictions. Some modelling studies, which did not account for the latent heat of evaporation (Cai et al, 2014;Chandramohan, 2015;Esfahani et al, 2014), found a steadily increasing temperature without this initial temperature drop.…”
Section: General Drying Characteristicsmentioning
confidence: 99%
“…Increase the drying temperature from 313 to 353 degrees Celsius, and you will save around 40% of the drying time, according to research [ 32 ]. Furthermore, with constant and varied surface transfer coefficients, the distribution of moisture did not change any more than before [ 33 ]. Tables 1 and Tables 2 provide the governing equations and boundary conditions, respectively, which are utilized in the food sector for modeling to dry products and ingredients.…”
Section: Main Textmentioning
confidence: 99%